2013
DOI: 10.1371/journal.pone.0072381
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Copy Number Variation in Sporadic Amyotrophic Lateral Sclerosis in the Turkish Population: Deletion of EPHA3 Is a Possible Protective Factor

Abstract: The genome-wide presence of copy number variations (CNVs), which was shown to affect the expression and function of genes, has been recently suggested to confer risk for various human disorders, including Amyotrophic Lateral Sclerosis (ALS). We have performed a genome-wide CNV analysis using PennCNV tool and 733K GWAS data of 117 Turkish ALS patients and 109 matched healthy controls. Case-control association analyses have implicated the presence of both common (>5%) and rare (<5%) CNVs in the Turkish populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…It has to be admitted, that some potentially harmless MG-CNVs have already been linked in population studies to an enhanced or diminish susceptibility for special disorders or (age-related) diseases. However, mechanisms, therefore, are still not understood yet 14 .…”
Section: Discussionmentioning
confidence: 99%
“…It has to be admitted, that some potentially harmless MG-CNVs have already been linked in population studies to an enhanced or diminish susceptibility for special disorders or (age-related) diseases. However, mechanisms, therefore, are still not understood yet 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that genomic deletions affecting DPYD occurred in 7% of pediatric patients with a complete DPD deficiency (van Kuilenburg et al., ). Genomic rearrangements in DPYD have also been observed in patients with ID (Willemsen et al., ), autism‐spectrum disorder (Carter et al., ; Prasad et al., ), syndromic obesity (D'Angelo, Moller Dos Santos, Alonso, & Koiffmann, ), and amyotrophic lateral sclerosis (Uyan et al., ). To date, no clear genotype–phenotype correlation has been established in patients with a DPD deficiency but it is noteworthy that patients with gross deletions in DPYD presented with a severe phenotype when compared with that observed in other DPD patients (van Kuilenburg et al., ).…”
Section: Genotype and Biochemical Phenotype Of A Family With Dpd Defimentioning
confidence: 97%
“…In addition, there have been studies of copy number variation (Blauw et al, 2008; Cronin et al, 2008; Wain et al, 2009; Blauw et al, 2010; Uyan et al 2013), a study specifically focusing on homozygosity segments (Mok et al 2013), and a pooling GWAS combined with pathway analysis (Xie et al, 2014). …”
Section: Genes Identified Through the Application Of Advanced Genomentioning
confidence: 99%
“…Similar to single nucleotide polymorphisms (SNPs), copy number variants are detected in healthy people. Several surveys have been performed in attempt to evaluate the involvement of copy number variants in ALS (Blauw et al, 2008; Cronin et al, 2008; Wain et al, 2009; Soichet et al, 2009; Blauw et al, 2010; Uyan et al 2013), while others investigated specific categories of copy number variants including de novo copy number variants (Pamphlett and Morahan, 2011a), somatic copy number variants (Pamphlett and Morahan, 2011b; Pamphlett and Morahan, 2011c), and copy number variants in ALS-discordant monozygotic twin pairs (Pamphlett and Morahan, 2011c). Although many copy number variants that were specific to patients with ALS were detected, common copy number variants were not significantly associated to ALS in these studies.…”
Section: Genes Identified Through the Application Of Advanced Genomentioning
confidence: 99%
See 1 more Smart Citation